PERson-centredness in hypertension management using information technology (PERHIT): a protocol for a randomised controlled trial in primary health care. (3rd May 2020) - Midlöv, Patrik; Nilsson, Peter M.; Bengtsson, Ulrika; Hoffmann, Mikael; Wennersten, André; Andersson, Ulrika; Malmqvist, Ulf; Steen Carlsson, Katarina; Ranerup, Agneta; Kjellgren, Karin
Abstract: Purpose: For primary health care (PHC), hypertension is the number one diagnosis for planned health care visits. The treatment of high blood pressure (BP) and its consequences constitutes a substantial economic burden. In spite of efficient antihypertensive medications, a low percentage of patients reach a well-controlled BP. The PERson-centredness in Hypertension management using Information Technology (PERHIT) Study is a multicentre randomised controlled trial. PERHIT is designed to evaluate the effect of supporting self-management on systolic blood pressure by the use of information technology in Swedish primary health care. Materials and Methods: After inclusion, 900 patients from 36 PHC centres are randomised to two groups. In the intervention group, patients are provided with a self-management support system including a home-BP monitor and further requested to perform self-reports and measure BP every evening for eight consecutive weeks. In the control group, patients receive treatment as usual. Results: The primary outcome will be the change in systolic blood pressure in patients with hypertension. In addition, person-centredness, daily life activities, awareness of risk and health care costs will also be evaluated. Conclusion: The results of this randomised controlled trial with assessment of blood pressure and same-day self-reports will provide patients a tool to understand the interplay between blood pressure and lifestyle applicable to primary health care. The self-management support system may be of importance for improved adherence to treatment and persistence to treatment recommendations.